A framework of analytical methods for horizontal behaviours of monopiles under V-H-M loads in sand. Issue 3 (4th March 2022) - Mu, Linlong; Chen, Wei; Zhang, Yiming; Chen, Xiaoxiang; Li, Wan
Abstract: The piles of offshore wind turbines are always subjected to multidirectional loads. The vertical and lateral behaviours of piles are designed separately in practice. However, many studies have shown that the vertical load has a substantial influence on the lateral behaviours of piles. The influence of the vertical load on the lateral behaviours of monopiles can be divided into three aspects: (1) the influence of the friction stress on the ultimate resistance p u of the p - y curve, (2) the P -Δ effect, and (3) the M R effect induced by the uneven distribution of vertical skin friction. Based on the passive wedge theory and the influence of the ultimate soil resistance per unit length p u caused by the vertical loads, the corrected p - y curve for sand is obtained. Considering the P -Δ effect and MR effect, an analytical method for monopiles under combined loads, including the lateral load, vertical load and moment, in sand is proposed based on the elastic-foundation beam theory coupled with p-y curves. The method is verified by analysing several existing cases. The capability of the proposed method to reasonably calculate the responses of monopiles under multidirectional loads in sand has been verified.